Gender matters: Experiences and consequences of digital dating abuse victimization in adolescent dating relationships. (3rd June 2017) - Reed, Lauren A.; Tolman, Richard M.; Ward, L. Monique
ABSTRACT: Digital dating abuse (DDA) behaviors include the use of digital media to monitor, control, threaten, harass, pressure, or coerce a dating partner. In this study, 703 high school students reported on the frequency of DDA victimization, whether they were upset by these incidents, and how they responded. Results suggest that although both girls and boys experienced DDA at similar rates of frequency (with the exception of sexual coercion), girls reported that they were more upset by these behaviors. Girls also expressed more negative emotional responses to DDA victimization than boys. Although DDA is potentially harmful for all youth, gender matters. These findings suggest that the experience and consequences of DDA may be particularly detrimental for girls.